Effect of Bacillus firmus Bacteria on Total Vibrio harveyi Bacteria and Vanname Shrimp Survival (Litopenaeus vannamei) - Yuli Anis Safitri (Central Research Institute For Agriculture, 2021)
The purpose of this study was to determine the effect of Bacillus firmus on the number of V. harveyi bacteria and the survival of the vanname shrimp (Litopenaeus vannamei). The main parameters in this study were the number of V. harveyi bacteria and the survival of the vanname shrimp (L. vanname), while the supporting parameters used were water quality including temperature, DO, pH and salinity The results showed the number of V. harveyi bacteria in the media maintenance of vanname shrimp after administration of B. firmus decreased from the first to the third day and increased on the fourth day of the infection period. When compared to the control without giving B. firmus, the number of V. harveyi bacteria actually increased compared to the treatment with B. firmus bacteria. Based on the results of the analysis of variance, it showed that giving B. firmus at different doses did not have a significantly different effect on the growth of V. harveyi but when compared to controls, it showed that giving B. firmus gave better results than without giving B. .firmus. Giving B. firmus bacteria with a density of 102 cfu/ml, 104 cfu/ml and 106 cfu/ml was able to reduce the number of V. harveyi compared to without B. firmus administration. cfu/ml because with a density of 102 cfu/ml it has been able to reduce the number of V. harveyi bacteria. The survival of vanname shrimp in the treatment of firmus bacteria obtained quite high results when compared to the control. giving B. firmus at a density of 106 was 87.5%, without giving B. firmus at 58.5%. Based on the results of analysis of variance on the vanname shrimp survival rate, it was found that there was no significant difference between treatments.